Pengaruh Fatigue Management berbasis Community Palliative Care terhadap Uncertainty in Illness pada Pasien Kanker Payudara - Nurul Nisah; Dewi Sartika; Diana Lestari (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Cancer-related fatigue (CRF) represents a persistent clinical manifestation that can potentially escalate uncertainty in illness among individuals with advanced breast cancer. This quasi-experimental study aimed to evaluate the efficacy of a community palliative care-based fatigue management intervention in attenuating uncertainty in illness among breast cancer patients. Employing a pretest-posttest control group design, a sample of 60 stage III and IV patients was selected using a purposive sampling technique and assigned to either an intervention group (n=30) or a control group (n=30). The intervention group underwent a structured four-week program integrating home visits and daily monitoring by community health cadres, which encompassed energy conservation education, structured physical activity, sleep hygiene, and psychosocial coping reinforcement, whereas the control group received routine primary care. Outcome measures included the Brief Fatigue Inventory (BFI) and the Mishel Uncertainty in Illness Scale (MUIS), with data analyzed using paired t-tests and independent t-tests. The intervention group demonstrated a statistically significant reduction in illness uncertainty scores from 78.45 ± 6.12 to 52.30 ± 5.45 (p < 0.001), whereas the control group showed no statistically significant change (77.90 ± 5.80 to 75.10 ± 6.05; p = 0.082). These findings confirm a pronounced and statistically significant mean difference between the two groups (p < 0.001). This study concludes that community palliative care-based fatigue management effectively reduces uncertainty in illness by redefining symptom ambiguity and restoring perceived control. Integrating structured symptom management into primary care facilities constitutes a critical foundation for minimizing the psychosocial burden in patients with advanced cancer.